Peran Sistem Volunteered Geographic Information (VGI) Sistem dalam Pengurangan Risiko Bencana: Konsep dan Implementasi - Dian Nuraini Melati (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2020)
There have been a lot of geospatial technologies implemented to support disaster management into a more effective way and achieve disaster risk reduction. One of these technologies is the use Volunteered Geographic Information (VGI). VGI refers to the volunteered activities by anyone to create geographic information. The recent development of VGI is obviously supported by the development technology itself such as social media, Global Positioning System (GPS) with acceptable accuracy. In addition, it is also supported by mostly unlimited cloud-based storage as well as smartphones. In the phenomena of natural disater such as flood, landslide, earth quake, tsunami, and other phenomena, the need of geospatial data and the availability in timely manner becomes important and crucial at all disaster management aspects. The availability of geographic information is very much critical at the time the disaster occurs compared to normal situation. Therefore, VGI is necessary in supporting near real time information. In this case, VGI has a key role in disaster management particularly to reduce disaster risk.